Inflammatory signals from fatty bone marrow support DNMT3A driven clonal hematopoiesis - Zioni, Naama; Bercovich, A. Akhiad; Chapal-Ilani, N.; Bacharach, Tal; Rappoport, N.; Solomon, A.; Avraham, R.; Kopitman, E.; Porat, Z.; Sacma, M.; Hartmut, G.; Scheller, Marina; et al. (Nature Communications, 2023)
Both fatty bone marrow (FBM) and somatic mutations in hematopoietic stem cells (HSCs), also termed clonal hematopoiesis (CH) accumulate with human aging. However it remains unclear whether FBM can modify the evolution of CH. To address this question, we herein present the interaction between CH and FBM in two preclinical male mouse models: after sub-lethal irradiation or after castration. An adipogenesis inhibitor (PPARγ inhibitor) is used in both models as a control. A significant increase in self-renewal can be detected in both human and rodent DNMT3AMut-HSCs when exposed to FBM. DNMT3AMut-HSCs derived from older mice interacting with FBM have even higher self-renewal in comparison to DNMT3AMut-HSCs derived from younger mice. Single cell RNA-sequencing on rodent HSCs after exposing them to FBM reveal a 6-10 fold increase in DNMT3AMut-HSCs and an activated inflammatory signaling. Cytokine analysis of BM fluid and BM derived adipocytes grown in vitro demonstrates an increased IL-6 levels under FBM conditions. Anti-IL-6 neutralizing antibodies significantly reduce the selective advantage of DNMT3AMut-HSCs exposed to FBM. Overall, paracrine FBM inflammatory signals promote DNMT3A-driven clonal hematopoiesis, which can be inhibited by blocking the IL-6 pathway.